The Features of Uzbek and English Stories - Baxtiyorovna, Jamolova Mohigul; Nurnazarovna, Soliyeva Muqaddas (Journal of Sustainability in Integrated Policy and Practice, 2024)
This article shows the importance of Uzbek and English stories in the development of a child by providing examples of stories and comparing them.